Management accounting in Portuguese hotel enterprises : update research - Santos, Luís Lima (2013)
Management accounting (MA) techniques have evolved in the recent years in the various companies. We have studied the MA techniques that are currently being used by different types of hotels. The sample includes 61 hotels, which were analyzed between 2010 and 2012. MA is a tool incorporated in the daily management practices of Portuguese hotels. However, we verified that the hotels have different behaviors in this area, which entailed a comprehensive study on the causes of this diversity. We applied the contingency theory to explain our findings, because this theory is based on the premise that the MA techniques are not used equally by all organizations.